A Packet Delay Assessment Model in the Data Link Layer of the LTE - Ulugbek Amirsaidov; Azamat Qodirov (JOIV : International Journal on Informatics Visualization, 2021)
The issues of modeling and evaluating the characteristics of the LTE data link layer functioning are considered. Transmitting packets in the data link layer are represented by a probabilistic-temporal graph consisting of two subgraphs. The ﬁrst subgraph describes the operation of the HARQ protocol, and the second subgraph describes the operation of the ARQ protocol. The ﬁrst subgraph is nested within the second subgraph. The probabilities of correct reception, non-error detection, and retransmission of packets in the MAC and RLC layers and generating functions of the packet service time based on the HARQ and ARQ protocols are determined. With the help of generating functions, the average value, variance, and coeﬃcient of variation of the packet service time are determined. To calculate the average packet delay time in the LTE data link layer, the type of queuing system is selected, taking into account the coeﬃcient of variation of the packet service time. The analysis of packets' delay time in the network's data link layer is carried out for diﬀerent values of the intensity of packet arrival and the probabilities of a bit error in the physical layer of the network. For the sustainable functioning of the data link layer of the network, the limit values of the intensity of the arrival of packets are determined for a given probability of a bit error in the physical layer of the network.